2022
DOI: 10.1021/acs.orglett.2c00962
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Asymmetric Dearomative Carbonylation of Indoles

Abstract: Herein, we disclose a strategy for the asymmetric dearomatization of N-arylacyl indoles via a palladium-catalyzed tandem Heck/carbonylation, leading to an array of indoline-3carboxylates bearing vicinal C2-aza-quaternary and C3 tertiary stereocenters in high yields and excellent enantio-and diastereoselectivities. This study is an important advance in the field of asymmetric carbonylation and enantioselective dearomatization reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 66 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…A novel methodology for the asymmetric dearomatization of N ‐arylacyl indoles was described in 2022 by Yao and Lin on the basis of an enantioselective palladium‐catalyzed domino Heck/esterification reaction [20] . This three‐component reaction occurred at 100 °C in MTBE as solvent between N ‐arylacyl indoles 46 , alcohols 47 and CO (1 atm) in the presence of TEA as base and a chiral catalyst in situ generated from 5 mol% of Pd 2 (dba) 3 and 20 mol% of chiral phosphoramidate ligand 48 .…”
Section: Enantioselective Palladium‐catalyzed Domino Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel methodology for the asymmetric dearomatization of N ‐arylacyl indoles was described in 2022 by Yao and Lin on the basis of an enantioselective palladium‐catalyzed domino Heck/esterification reaction [20] . This three‐component reaction occurred at 100 °C in MTBE as solvent between N ‐arylacyl indoles 46 , alcohols 47 and CO (1 atm) in the presence of TEA as base and a chiral catalyst in situ generated from 5 mol% of Pd 2 (dba) 3 and 20 mol% of chiral phosphoramidate ligand 48 .…”
Section: Enantioselective Palladium‐catalyzed Domino Reactionsmentioning
confidence: 99%
“…A novel methodology for the asymmetric dearomatization of N-arylacyl indoles was described in 2022 by Yao and Lin on the basis of an enantioselective palladium-catalyzed domino Heck/esterification reaction. [20] This three-component reaction occurred at 100 °C in MTBE as solvent between N-arylacyl indoles 46, alcohols 47 and CO (1 atm) in the presence of TEA as base and a chiral catalyst in situ generated from 5 mol% of Pd 2 (dba) 3 and 20 mol% of chiral phosphoramidate ligand 48. It resulted in the formation of a wide range of chiral indoline-3-carboxylates 49 bear-ing vicinal C2-aza-quaternary and C3 tertiary stereocenters with moderate to excellent yields (51-95%) and uniformly high enantioselectivities (83-97% ee), as illustrated in Scheme 12.…”
Section: Hélène Pellissier Carried Out Her Phd Under the Supervision ...mentioning
confidence: 99%
“…5 However, the corresponding asymmetric dearomatization remains a challenging task and the successful cases are very scarce yet. 6,7 For example, Jia et al pioneeringly reported a palladium-catalyzed intramolecular asymmetric arylative dearomatization of indoles, 6 a and several intermolecular asymmetric dearomative difunctionalization reactions of indoles with nucleophiles have recently been achieved via palladium catalysis by the groups of Jia, Lautens, Liang and Yao (Fig. 1b, i).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Even though many new Pd-catalyzed carbonylations have been demonstrated, no example of carbonylative dearomatization via an 15 Recently, Yao and co-workers reported a Pd-catalyzed enantioselective dearomative carbonylation of N-arylacyl indoles that provided access to a series of nonspirocyclic indoline-3-carboxylate derivatives. 16 Notably, Studer demonstrated an asymmetric dearomatization of indoles to carbonylcontaining spiroindolenines catalyzed by NHC in 2017. The bromide group was converted into a formyl group under harsh conditions involving t BuLi, and then the aldehyde was cyclized to the spiroindolenine, which limited the functional group tolerance to some extent.…”
mentioning
confidence: 99%
“…Afterward, Wu and co-workers developed a Pd-catalyzed Heck carbonylation/dearomatization of N -(2-bromobenzoyl)­indoles leading to nonspirocyclic indoline esters and amides . Recently, Yao and co-workers reported a Pd-catalyzed enantioselective dearomative carbonylation of N -arylacyl indoles that provided access to a series of nonspirocyclic indoline-3-carboxylate derivatives . Notably, Studer demonstrated an asymmetric dearomatization of indoles to carbonyl-containing spiroindolenines catalyzed by NHC in 2017.…”
mentioning
confidence: 99%